2015
DOI: 10.1680/macr.14.00239
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of dynamic behaviour of RC beams under cyclic loading with different loading rates

Abstract: The dynamic behaviours of reinforced concrete (RC) beams are inevitably affected by loading rates. The effects of loading rate on the dynamic behaviour of RC bending beams under cyclic loading were studied numerically. An analysis of a two-dimensional finite-element model of RC beams, with the rate-independent and rate-dependent Drucker-Prager (DP) concrete models and two rate-dependent steel reinforcement models, was carried out. Cyclic loading was displacement-controlled with imposed loading rates of 0 . 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…According of numerical simulation results on RC structural members under dynamic loading [58,115,117,119,170,171], it can be concluded that with the increase of loading rate, the bearing capacity and stiffness of structural members are enhanced whereas the deformation ductility is likely to be decreased. These numerical findings are in good agreement with the available dynamic loading test observations.…”
Section: Discussion On Numerical Simulation Workmentioning
confidence: 99%
See 2 more Smart Citations
“…According of numerical simulation results on RC structural members under dynamic loading [58,115,117,119,170,171], it can be concluded that with the increase of loading rate, the bearing capacity and stiffness of structural members are enhanced whereas the deformation ductility is likely to be decreased. These numerical findings are in good agreement with the available dynamic loading test observations.…”
Section: Discussion On Numerical Simulation Workmentioning
confidence: 99%
“…These numerical findings are in good agreement with the available dynamic loading test observations. It has also been shown in a few studies the cracking pattern, damage and failure mode can be well through numerical analysis [58,117,129,130]. Moreover, parametric studies have been carried out to investigate the influences of structural parameters on the dynamic behaviors of RC structural members [15,58,116,171].…”
Section: Discussion On Numerical Simulation Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For the steel bars (including longitudinal rebar and stirrups), a bilinear elasto-plastic model with kinematic hardening was adopted and this was similar with that in Xiao (2015). As shown in Figure 13(b), o–a is the elastic stage, a–b is the hardening stage, and the harding modulus (i.e.…”
Section: Fe Simulationmentioning
confidence: 99%
“…Among them, the experimental method [9] is the most convincing; however, the test data are limited due to the large financial and human costs. As an alternative, some scholars have made attempts to establish numerical models to simulate the dynamic mechanical behaviors of structural members [10][11][12][13] and further develop empirical models of dynamic increase factor (DIF) to estimate the critical mechanical behavior parameters [14][15][16][17]. Based on the dynamic loading test results and the Bayesian updating method, Li et al [18] developed predictive models of the dynamic modified coefficient (DMC) for RC columns, which can be used to estimate the dynamic mechanical behaviors of RC columns under seismic loading.…”
Section: Introductionmentioning
confidence: 99%